A pregnancy complication-dependent change in SIgA-targeted microbiota during third trimester. Issue 2 (29th January 2020) - Cui, Mengjun; Qi, Ce; Yang, Liping; Zhang, Mengyun; Wang, Huiyan; She, Guangtong; Yu, Renqiang; Miao, Tingting; Sun, Jin
Abstract : Complications in the third trimester were related to disorders of the intestinal SIgA-targeted microbiota. Abstract : Gut microbiota play a crucial role in metabolic dysfunction during gestation, which might be prevented by using probiotics. This study compared the composition of the gut microbiota in healthy and complicated pregnancies, for screening and isolating healthy pregnancy-derived probiotics. According to the principal component analysis of secretory immunoglobulin A (SIgA)-coated microbiota in the gut, third-trimester volunteers can be divided into three groups: AHd ( n = 29), GDMd ( n = 37), and GHd ( n = 25), dominated by asymptomatic healthy donors (62.07%), gestational diabetes mellitus (GDM) donors (40.54%), and gestational hypertension (GH) donors (40%), respectively. There was a significant difference in β-diversity ( p < 0.01) and α-diversity ( p < 0.05) among the three groups. At the phylum level, the Firmicutes of the GHd group were significantly lower than those of the AHd group ( p = 0.039), while Bacteroidetes ( p = 0.005) and Proteobacteria ( p = 0.002) of the GHd group were more dominant than those of the AHd group. At the genus level, the linear discriminant analysis effect size showed that SIgA-targeted Enterococcus was the dominant taxonomic biomarker of the AHd group, and the GHd group was enriched with Escherichia and Streptococcus . The GDMd and GHd groups had higher faecal calprotectin, serum lipopolysaccharide, zonulin, and GLYCAM-1 levels. We conclude that the occurrence of complications in the third trimester may be related to intestinal barrier injury associated with disorders of the intestinal SIgA-targeted microbiota; gut barrier injury triggers inflammation in pregnant women. SIgA-targeted L. reuteri showed a significant correlation with low inflammatory response and may be a potential probiotic candidate for preventing pregnancy complications.